منهج القرآن الكريم في تأصيل قاعدة سد الذرائع - جميلة إسماعيل; مريم مصباح; يسرى فاطنة طيبي; د/بن لسبط لدمبة (جامعة عمار ثليجي الاغواط, 2023)
ص: لمد تكلمنا ف مذكرتنا هذه عن موضوع منهج المرآن الكر مٌ ف تؤص لٌ لاعدة سد الذرائع، و تعرفنا على ماه ةٌ هذه الماعدة، وب نٌا مشروع تٌها، و الأدلة الت تمدم عل هٌا من الكتاب و السنة، ومدى شمول ةٌ المرآن الكر مٌ لها الذي عٌط المنع و الدرع لكل مداخل ووسائل الحرام، و ك فٌ ةٌ اعتناء المفسر نٌ لهذه الماعدة، وذكرنا بعض النماذج و التطب مٌات ف مجال العم دٌة و الاسرة و المعاملات الت تب نٌ أن سد الذرائع عٌتبر وال اٌ و سورا من عٌا لحما ةٌ الشرع ف مختلف الأزمنة من المفاسد كلها. Abstract: In this note, we have talked about the topic of the Holy Qur’an’s methodology in rooting the rule of blocking pretexts, and we got acquainted with what this rule is, and we explained its legitimacy and the evidence that was presented to it from the Book and the Sunnah, and the extent of the comprehensiveness of the Holy Qur’an to it, which gives prevention and a shield to all entrances and means of what is forbidden, and how The interpreters pay attention to this rule, and we mentioned some models and applications in the field of belief, family and transactions that show that blocking pretexts is considered a protective and impenetrable wall to protect the Sharia in different times from all evils.